Impact of Foreign Direct Investment Policy on the Economy in Indonesia - M Yazhar Rayhan Al Farrasy; Nur Hidayatul Fithri (Magister Ilmu Hukum Fakultas Hukum Universitas Riau, 2024)
Given the large number of investors who are starting to be interested in the State of Indonesia, studies related to foreign investment legal policies need to be carried out. The specific purpose of this paper is to see how the economic impact of foreign investment in Indonesia will be. The method to be carried out is Normative Juridical with a legal approach. There are two types of investment in Indonesia, namely Domestic Investment and Foreign Investment. Foreign Direct Investment has a significant impact on economic growth in Indonesia, because foreign investment can create jobs, and opening new job opportunities in developing countries. FDI is one of the sources of state financial savings in line with the increasing economic increase due to investment from foreign parties who invest. With the existence of PMA, the government establishes policies that have been regulated in Law No. 25 of 2007 Article 4.